The Role of Village-Owned Enterprises (BUMDes) in Empowering the Community of Kalukubula Village - Yuniati Santi Tikara; Edhi Taqwa; Yunus Sading; Andi Herman Jaya; Musdayati Musdayati (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This research aims to determine the role of BUMDes Mutianggaluku Mandiri in empowering the community in Kalukubula Village. Methodology/approach: This study used a descriptive qualitative approach and was conducted from March to May 2024 in Kalukubula Village, Sigi Biromaru District. Data were collected through interviews and field observations involving village officials, BUMDes managers, and residents, and were analyzed through data reduction, data display, and conclusion drawing. Results/findings: Based on the research results, it was found that the various types of businesses managed by BUMDes Mutianggaluku Mandiri are part of an empowerment system, where the aim of empowerment is to help the community become more prosperous. Conclusion: BUMDes Mutianggaluku Mandiri empowers Kalukubula through local businesses that increase income and jobs. To grow effectively, it needs better training, transparency, and community involvement. Limitations: This study, limited to Kalukubula, lacks generalizability and in-depth analysis. Limited expertise in BUMDes also hinders optimal management. Contribution: This study highlights BUMDes’ role in community empowerment through local business management and serves as input for improving its performance and impact.